A resorufin-based fluorescent turn-on probe responsive to nitroreductase activity and its application to bacterial detection. (December 2019) - Yoon, Jung Won; Kim, Sejeong; Yoon, Yohan; Lee, Min Hee
Abstract: We present two resorufin-based fluorescent turn-on probes responsive to nitroreductase (NTR) activity (NTR probes1 and2 ) and their use toward the detection of bacteria. The probes exhibit a fluorescence turn-on at 586 nm in response to NTR activity, which corresponds to a vivid pink color. These optical changes are based on the NTR-mediated reduction of the nitro groups in the probes, which results in the production of highly fluorescent resorufin. The detection ability, mechanism, and enzyme kinetics of the probes for NTR activity have been thoroughly investigated. The enzyme efficiencies of the probes were superior to those previously reported. In addition, NTR probe1 exhibited an excellent detection ability for NTR with high selectivity and no background signal when compared to2 . Moreover, NTR probe1 was applicable for bacterial detection using a wash-free process because it gave rise to a fluorescence turn-on signal in response to bacterial NTR activity. Graphical abstract: Image 1 Highlights: Resorufin-based fluorescent turn-on probes1 and2 were developed for detecting nitroreductase (NTR) activity. The probes showed a fluorescence turn-on signal with a vivid pink color to NTR activity. The probes exhibited moderate response time to NTR activity with a high enzyme efficiency. The NTR probe1 exhibited a superior detection ability for NTR activity to probe2. The NTR probe1 can act as a fluorescent turn-on probe for bacterial detection.